Key factors for successful implementation of the independent curriculum: examining teacher readiness - Retnowati, Ayu Ana Fitri; Triyanto, Triyanto; Matsuri, Matsuri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The Merdeka Curriculum that prioritizes student autonomy in the learning process was chosen as a solution to overcome the learning crisis exacerbated by the Covid-19 pandemic. However, the implementation of this curriculum faces challenges, especially related to teacher readiness. This study aims to analyze factors that affect teacher readiness in implementing the